FEATURES OF ROMANTICISM AS a CREATIVITY TYPE OF VELIMIR KHLEBNIKOV’S CREATIVE STYLE (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-4-141-152Velimir Khlebnikov was one of the most prominent figures of the Silver Age epoch, neoromantic by its characteristics. At the same time, his creative style is formed not only under the influence of the cultural epoch dominants, but it is also structured as the realization of one of the two main types of creativity that Zh. de Stal`, P.N. Sakulin, V.M. Zhirmunskij, A.S. Pushkin and other wrote about. This refers to the romantic style suggesting the desire to overcome the boundaries of time and space, eternal aspiration and dissatisfaction and related characteristic forms of genre and artistic synthesis. This problem is considered on examples of the following works: play «Mirskoncza», story «Ka», super story «Zangezi», poems «Ya ne znayu, Zemlya kruzhitsya ili net…», «Segodnya snova ya pojdu…», «Ya vy`shel yunoshej odin…», «Trushhoby» as well as articles of different years. Key words: Velimir Khlebnikov, romanticism, creativity type, romantic aesthetic, writing